Efficient and Highly Transparent Ultra‐Thin Nickel‐Iron Oxy‐hydroxide Catalyst for Oxygen Evolution Prepared by Successive Ionic Layer Adsorption and Reaction. Issue 10 (18th July 2019) - Garcia‐Torregrosa, Ivan; Goryachev, Andrey; Hofmann, Jan P.; Hensen, Emiel J. M.; Weckhuysen, Bert M.
Abstract: NiFeOx thin films prepared by successive ionic layer adsorption and reaction (SILAR) were deposited onto nanostructured hematite (Fe2 O3 ) photoanodes and their effect on the current density and photo‐onset potential was studied. After optimization of bath concentration, immersion times, and number of SILAR cycles, very conformal and active NiFeOx films with controlled Fe/Ni content ratios were obtained. Upon the incorporation of Fe 2+ species in the NiCl2 solution bath, a cathodic shift in the overpotential required for the oxygen evolution reaction (OER) by more than 200 mV with no decrease in current density was observed after 40 SILAR cycles. We demonstrate that by fine‐tuning the film composition and thickness, NiFeOx can be employed as an efficient OER catalyst with very low absorbance in the visible spectrum. By doing so, we demonstrate that this material has great potential for incorporation in semiconductor photoelectrodes for direct solar‐driven water electrolysis. Being a simple water‐based layer‐by‐layer growth method, SILAR offers promise for the synthesis of catalyst coatings in nano‐structured and high surface area electrodes. Abstract : Transparent catalyst : By fine‐tuning the film composition and thickness, NiFeOx can be employed as an efficient oxygen evolution reaction catalyst with very low absorbance in the visible spectrum. We demonstrate that this material has great potential for incorporation in semiconductor photoelectrodes for direct solar‐driven water electrolysis.